Preparation method of anticorrosive coating of environment-friendly copper alloy catenary part
Through the dual passivation treatment of biomass derivative arginine chromate and low chromium anhydride, the corrosion problem of copper alloy contact mesh components in the marine environment is solved, and a passivation coating with good weather resistance is formed, achieving environmentally friendly and long-term anti-corrosion effect.
Patent Information
- Application Number
- CN202510634141.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-08-08
AI Technical Summary
Existing copper alloy contact mesh parts are prone to corrosion in marine environments. The traditional anti-corrosion process is highly toxic, costly and has poor coating density, which cannot meet the needs of use under high-voltage electric fields.
The biomass derivative arginine chromate and low chromium anhydride are double passivation treatment to form a passivation coating with good weather resistance. The completeness of the coating is improved by primary and secondary chromate passivation treatments combined with polyethylene glycol.
It realizes environmentally friendly anti-corrosion coatings, extend service life, reduce environmental pollution, reduce maintenance frequency, and improve equipment reliability and operating efficiency.
Smart Images

Figure HDA0005406201900000011 
Figure HDA0005406201900000012 
Figure HDA0005406201900000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of anti-corrosion coatings, and in particular relates to a method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components. Background Art
[0002] Copper alloys are widely used in catenary components across the Gulf region due to their excellent electrical conductivity and mechanical properties. However, high concentrations of salt spray and moisture in marine environments can severely corrode copper alloys, leading to equipment failure and shortened service life. Therefore, developing an effective corrosion protection process to improve the corrosion resistance of copper alloy components is of great practical significance.
[0003] Anti-corrosion treatments for copper alloys include anodizing, chemical passivation, anti-corrosion coatings, electroplating, and spraying. Each of these methods has its own advantages and disadvantages. Coatings are prone to aging and damage, while spray coatings have weak adhesion and are susceptible to mechanical damage. Furthermore, copper alloy components in contact networks, which primarily serve as contact devices for transmission circuits, face stringent operating requirements. Even with the addition of large amounts of conductive fillers, anti-corrosion coatings such as zinc-rich coatings, epoxy coatings, and acrylic coatings cannot withstand high-voltage electric field conditions. Typically, these copper alloy components are treated with chemical passivation or electroplating, but the electroplating process is complex and costly. Traditional chemical passivation methods, such as chromate passivation, rely on hexavalent chromium, which is highly toxic and polluting, requiring high wastewater treatment costs. Furthermore, the resulting passivation coatings lack density, have a short salt spray corrosion resistance, and are prone to flaking in hot, humid, or acidic / alkaline environments.
[0004] By employing an environmentally friendly copper alloy anti-corrosion process, the present invention not only effectively extends the service life of copper alloy components but also reduces environmental pollution and health risks. These environmentally friendly processes typically use non-toxic or low-toxic chemical materials, avoiding the emission of harmful substances found in traditional processes, thereby protecting the health of operators and the surrounding environment. Furthermore, the implementation of these environmentally friendly anti-corrosion processes can reduce the frequency of maintenance and component replacement, thereby reducing equipment downtime and maintenance costs, and improving equipment operational efficiency and reliability.
[0005] Therefore, further exploring environmentally friendly copper alloy anti-corrosion technology and optimizing its preparation process have important practical application value and research significance. Summary of the Invention
[0006] The main purpose of the present invention is to address the problems existing in the existing copper alloy anti-corrosion process and provide an environmentally friendly method for preparing anti-corrosion coatings for copper alloy contact network components. The primary passivation uses a biomass derivative, arginine chromate, and the secondary passivation uses a low-chromium anhydride formula to synergistically enhance the corrosion resistance. Arginine chromate reduces the dependence on hexavalent chromium, and polyethylene glycol synergistically improves the integrity of the coating and reduces heavy metal pollution. The anti-corrosion coating preparation method has the advantages of being green and environmentally friendly, having a long anti-corrosion time, excellent adhesion, short drying time, and being environmentally friendly, and is suitable for promotion and application.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components, the specific process comprising: 1) pre-corrosion treatment, 2) primary chromate passivation treatment, 3) secondary chromate passivation treatment, and 4) drying.
[0009] 1) Pre-corrosion Treatment: Prepare a pre-corrosion treatment solution consisting of 0-5% glacial acetic acid, 0-5% concentrated hydrochloric acid, 0-5% sulfuric acid, and the remainder water by weight. Soak the copper alloy parts in the pre-corrosion treatment solution for 10-30 minutes. Rinse the copper alloy parts with running water for 30-60 minutes. Repeat this step 1-5 times.
[0010] 2) Primary Chromate Passivation: Prepare a primary chromate passivation solution by weight: 10-30% arginine chromate, 0-1% sulfuric acid, 0-1% phosphoric acid, 0-10% polyethylene glycol, and the remainder water. Soak the copper alloy parts in the primary chromate passivation solution for 10-30 minutes. Rinse the copper alloy parts under running water for 30-60 minutes. Repeat this step 1-5 times.
[0011] 3) Secondary Chromate Passivation: Prepare a secondary chromate passivation solution by weight: 1-5% chromic anhydride, 0-1% acetic acid, 1-5% copper sulfate, 1-5% sodium formate, and the remainder water. Immerse the copper alloy parts in the secondary chromate passivation solution for 10-30 minutes. Rinse the copper alloy parts under running water for 30-60 minutes. Repeat this step 1-5 times.
[0012] 4) Drying: Place the prepared parts in a dryer at 50-60 degrees Celsius for 1-2 days.
[0013] The preparation method of the arginine chromate is as follows: adding ethanol and water in a mass ratio of 1:2 to 2:1 into a container, accounting for a total of 50 to 65% by weight; then adding arginine and sodium chromate in a mass ratio of 1:2 to 2:1, accounting for a total of 20 to 50% by weight; slowly adding 5 to 10% by weight of a 0.1 to 0.5 mol / L hydrochloric acid solution dropwise at a stirring rate of 100 to 1000 rpm, concentrating at 50 to 100 degrees Celsius, and then vacuum drying. The resulting product is washed with a mixed solution of ethyl acetate and petroleum ether in a mass ratio of 1:1 to 1:2; and drying to obtain the arginine chromate.
[0014] Preferably, the pre-corrosion treatment liquid comprises the following components by mass: 2% glacial acetic acid, 1% concentrated hydrochloric acid, 0.25% sulfuric acid, and the remainder water.
[0015] Preferably, the primary chromate passivation treatment solution comprises, by mass percentage, 30% arginine chromate, 1% sulfuric acid, 1% phosphoric acid, 5% polyethylene glycol, and the remainder water.
[0016] Preferably, the secondary chromate passivation treatment solution comprises, by mass percentage, 3% chromic anhydride, 1% acetic acid, 2% copper sulfate, 1% sodium formate, and the remainder water.
[0017] The principle of the present invention is:
[0018] The present invention provides a method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components. Through a double passivation treatment of biomass arginine chromate + low chromic anhydride, a complete and weather-resistant passivation coating can be formed on the surface of the copper alloy components. After the chromate contacts the metal surface, it can form a thin passivation film through adsorption. This film can effectively prevent the redox reaction from occurring, thereby reducing the occurrence of corrosion. The passivation treatment liquid prepared based on biomass arginine chromate can form a complex coating with the function of a vapor phase corrosion inhibitor on the surface of the copper alloy components, which can improve the anti-rust effect through a synergistic effect and enhance the performance of the vapor phase inhibitor. In addition, the addition of oligomer polyethylene glycol helps to improve the integrity and weather resistance of the coating, significantly improving the corrosion resistance while reducing the amount of hexavalent chromium used.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) The anti-corrosion coating preparation method obtained by the present invention has the advantages of long anti-corrosion time, long service life, good weather resistance, good decorativeness, water-based and environmentally friendly; and the construction preparation involved is simple, the anti-corrosion effect is good, and it is suitable for promotion and application.
[0021] 2) The anti-corrosion coating preparation method obtained by the present invention can form a complete, weather-resistant passivation coating on the surface of copper alloy parts through secondary chromate treatment.
[0022] 3) The present invention provides a method for an environmentally friendly chromate treatment solution, which can form a complex coating with a vapor phase corrosion inhibitor function on the surface of copper alloy through passivation treatment of arginine chromate, a biomass derivative, and synergistically improve the anti-rust effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a comparison of the morphology of the copper alloy component obtained in Example 1 before and after the simulated cross-bay area salt spray test;
[0024] Figure 2 This is a comparison of the morphology of the copper alloy component obtained in Example 2 before and after the simulated cross-bay area salt spray test;
[0025] Figure 3 This is a comparison of the morphology of the copper alloy component obtained in Example 3 before and after the simulated cross-bay area salt spray test;
[0026] Figure 4 This is a comparison of the morphology of the copper alloy component obtained in Example 4 before and after the simulated cross-bay area salt spray test;
[0027] Figure 5 This is a comparison of the morphology of the copper alloy component obtained in Comparative Example 1 before and after the simulated cross-bay area salt spray test;
[0028] Figure 6 This is a comparison of the morphology of the copper alloy component obtained in Comparative Example 2 before and after the simulated cross-bay area salt spray test;
[0029] Figure 7 This is a comparison of the morphology of the copper alloy component obtained in Comparative Example 3 before and after the simulated cross-bay area salt spray test;
[0030] Figure 8 This is a comparison of the morphology of the copper alloy component obtained in Comparative Example 4 before and after the simulated cross-bay area salt spray test;
[0031] Figure 9 This is a comparison of the morphology of the copper alloy component obtained in Comparative Example 5 before and after the simulated cross-bay area salt spray test;
[0032] Figure 10 This is a comparison of the morphology of the copper alloy component obtained in Comparative Example 6 before and after the simulated cross-bay area salt spray test;
[0033] Figure 11 Nyquist plots of electrochemical impedance spectroscopy of the copper alloy parts obtained in Example 1 and Comparative Example 1;
[0034] Figure 12 Bode impedance diagrams of electrochemical impedance spectroscopy of copper alloy parts obtained in Example 1 and Comparative Example 1;
[0035] Figure 13 BodeBode phase diagram of the electrochemical impedance spectroscopy of the copper alloy parts obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0037] In the following examples, the molecular weight of the polyethylene glycol used was 1000.
[0038] In the following examples, the arginine chromate used was prepared by the following steps:
[0039] Ethanol and water in a mass ratio of 1:1 are added to a container, accounting for a total of 60% by weight; arginine and sodium chromate in a mass ratio of 1:1 are then added, accounting for a total of 35% by weight; a stirring rate of 800 rpm is maintained, and 5% by weight of a 0.1-0.5 mol / L hydrochloric acid solution is slowly added dropwise. The mixture is concentrated at 90 degrees Celsius and then vacuum dried. The resulting product is washed with a mixed solution of ethyl acetate and petroleum ether in a mass ratio of 1:1.25 and dried to obtain arginine chromate.
[0040] Example 1
[0041] A method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components, the specific process is as follows:
[0042] 1) Pre-corrosion Treatment: Prepare a pre-corrosion treatment solution consisting of 2% glacial acetic acid, 1% concentrated hydrochloric acid, 0.25% sulfuric acid, and the remainder water. Soak the copper alloy parts in the pre-corrosion treatment solution for 20 minutes. Rinse the copper alloy parts with running water for 40 minutes. Repeat this step once.
[0043] 2) Primary Chromate Passivation: Prepare a primary chromate passivation solution containing 30% arginine chromate, 1% sulfuric acid, 1% phosphoric acid, 5% polyethylene glycol, and the remainder water. Immerse the copper alloy component in the primary chromate passivation solution for 20 minutes. Rinse the copper alloy component under running water for 40 minutes. Repeat this process once.
[0044] 3) Secondary chromate passivation: Prepare secondary chromate passivation solution according to the following ratio: 3% chromic anhydride, 1% acetic acid, 2% copper sulfate, 1% sodium formate, and the remainder water. Soak the copper alloy parts in the secondary chromate passivation solution for 20 minutes. Rinse the copper alloy parts with running water for 40 minutes. Repeat the above steps once.
[0045] 4) Drying: The prepared parts were placed in a dryer at 55 degrees Celsius for 1 day.
[0046] Example 2
[0047] Compared with Example 1, Example 2 differs in that the treatment liquid is different, and other operations are the same as Example 1.
[0048] A method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components, the specific process comprising: 1) pre-corrosion treatment, 2) primary chromate passivation treatment, 3) secondary chromate passivation treatment, and 4) drying.
[0049] The components and their mass percentages in each treatment solution include: 1) pre-corrosion treatment solution: 2% glacial acetic acid, 1% concentrated hydrochloric acid, 0.25% sulfuric acid, and the remainder water; 2) primary passivation treatment solution: 20% arginine chromate, 1% sulfuric acid, 1% phosphoric acid, 5% polyethylene glycol, and the remainder water; 3) secondary passivation treatment solution: 3% chromic anhydride, 1% acetic acid, 2% copper sulfate, 1% sodium formate, and the remainder water.
[0050] Example 3
[0051] Compared with Example 1, Example 3 differs in that the treatment liquids are different, and other operations are the same as Example 1.
[0052] A method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components, the specific process comprising: 1) pre-corrosion treatment, 2) primary chromate passivation treatment, 3) secondary chromate passivation treatment, and 4) drying.
[0053] The components and their mass percentages in each treatment solution include: 1) pre-corrosion treatment solution: 2% glacial acetic acid, 1% concentrated hydrochloric acid, 0.25% sulfuric acid, and the remainder water; 2) primary passivation treatment solution: 10% arginine chromate, 1% sulfuric acid, 1% phosphoric acid, 5% polyethylene glycol, and the remainder water; 3) secondary passivation treatment solution: 3% chromic anhydride, 1% acetic acid, 2% copper sulfate, 1% sodium formate, and the remainder water.
[0054] Example 4
[0055] Compared with Example 1, Example 3 differs in that the treatment liquids are different, and other operations are the same as Example 1.
[0056] A method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components, the specific process comprising: 1) pre-corrosion treatment, 2) primary chromate passivation treatment, 3) secondary chromate passivation treatment, and 4) drying.
[0057] The components and their mass percentages in each treatment solution include: 1) pre-corrosion treatment solution: 2% glacial acetic acid, 1% concentrated hydrochloric acid, 0.25% sulfuric acid, and the remainder water; 2) primary passivation treatment solution: 40% arginine chromate, 1% sulfuric acid, 1% phosphoric acid, 5% polyethylene glycol, and the remainder water; 3) secondary passivation treatment solution: 3% chromic anhydride, 1% acetic acid, 2% copper sulfate, 1% sodium formate, and the remainder water.
[0058] Comparative Example 1
[0059] The difference between Comparative Example 1 and Example 1 is that the passivation treatment is different, and the other operations are the same as those of Example 1.
[0060] A method for preparing an anti-corrosion coating for a copper alloy component, the specific process comprising: 1) pre-corrosion treatment, 2) primary chromate passivation treatment, and 3) drying.
[0061] The components and their mass percentages in each treatment solution include: 1) pre-corrosion treatment solution: 2% glacial acetic acid, 1% concentrated hydrochloric acid, 0.25% sulfuric acid, and the rest water; 2) primary passivation treatment solution: 30% sodium dichromate, 1% sulfuric acid, 1% phosphoric acid, and the rest water.
[0062] Comparative Example 2
[0063] The main difference between Comparative Example 2 and Example 1 is that arginine chromate is replaced by sodium dichromate in the primary passivation treatment solution, and the other operations are the same as those in Example 1.
[0064] A method for preparing an anti-corrosion coating for a copper alloy component, the specific process comprising: 1) pre-corrosion treatment, 2) primary chromate passivation treatment, 3) secondary chromate passivation treatment, and 4) drying.
[0065] The components and their mass percentages in each treatment solution include: 1) pre-corrosion treatment solution: 2% glacial acetic acid, 1% concentrated hydrochloric acid, 0.25% sulfuric acid, and the remainder water; 2) primary passivation treatment solution: 30% sodium dichromate, 1% sulfuric acid, 1% phosphoric acid, 5% polyethylene glycol, and the remainder water; 3) secondary passivation treatment solution: 3% chromic anhydride, 1% acetic acid, 2% copper sulfate, 1% sodium formate, and the remainder water.
[0066] Comparative Example 3
[0067] Comparative Example 3 differs from Example 1 in that arginine chromate is not complexed to form arginine chromate, but arginine and sodium dichromate are directly added. Other operations are the same as in Example 1.
[0068] A method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components, the specific process comprising: 1) pre-corrosion treatment, 2) primary chromate passivation treatment, 3) secondary chromate passivation treatment, and 4) drying.
[0069] The primary chromate passivation treatment solution contains 12% arginine, 18% dichromate, 1% sulfuric acid, 1% phosphoric acid, 5% polyethylene glycol, and the remainder is water.
[0070] Comparative Example 4
[0071] The difference between Comparative Example 4 and Example 1 is that only one chromate passivation treatment is performed.
[0072] A method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components, the specific process is as follows:
[0073] 1) Pre-corrosion Treatment: Prepare a pre-corrosion treatment solution consisting of 2% glacial acetic acid, 1% concentrated hydrochloric acid, 0.25% sulfuric acid, and the remainder water. Soak the copper alloy parts in the pre-corrosion treatment solution for 10-30 minutes. Rinse the copper alloy parts with running water for 30-60 minutes. Repeat this step once.
[0074] 2) Chromate Passivation: Prepare a chromate passivation solution containing 30% arginine chromate, 1% sulfuric acid, 1% phosphoric acid, 5% polyethylene glycol, and the remainder water. Soak the copper alloy parts in the chromate passivation solution for 10-30 minutes. Rinse the copper alloy parts under running water for 30-60 minutes. Repeat this step once.
[0075] 3) Drying: Place the prepared parts in a dryer at 50-60 degrees Celsius for 1 day.
[0076] Comparative Example 5
[0077] Compared with Example 1, Comparative Example 5 is different in that only one chromate passivation treatment is performed.
[0078] A method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components, the specific process is as follows:
[0079] 1) Pre-corrosion Treatment: Prepare a pre-corrosion treatment solution consisting of 2% glacial acetic acid, 1% concentrated hydrochloric acid, 0.25% sulfuric acid, and the remainder water. Soak the copper alloy parts in the pre-corrosion treatment solution for 10-30 minutes. Rinse the copper alloy parts with running water for 30-60 minutes. Repeat this step once.
[0080] 2) Primary chromate passivation treatment: Prepare the chromate passivation solution according to the following ratio: 3% chromic anhydride, 1% acetic acid, 2% copper sulfate, 1% sodium formate, and the remainder water. Soak the copper alloy parts in the chromate passivation solution for 10 to 30 minutes. Rinse the copper alloy parts with running water for 30 to 60 minutes. Repeat the above steps once.
[0081] 3) Drying: Place the prepared parts in a dryer at 50-60 degrees Celsius for 1 day.
[0082] Comparative Example 6
[0083] Comparative Example 6 is compared with Example 1, except that the primary passivation solution does not contain polyethylene glycol, and the other operations are the same as those in Example 1.
[0084] The anti-corrosion coatings obtained in Examples 1 to 3 and the comparative example were subjected to salt spray tests simulating the cross-bay area environment. The results are shown in Table 1.
[0085] Simulated Trans-Bay Area Salt Spray Test: Conducted in accordance with the national standard GB / T 10125-2021, using a 5% sodium chloride solution at a temperature of 35±2°C. Hydrochloric acid was added to adjust the pH to 6.0-6.3. The test specimens were positioned at an angle of 15° to 30° for 72 hours. Figure 1-10 Comparison of the morphology of copper alloy components obtained in the Examples and Comparative Examples before and after a simulated cross-bay salt spray test. The left image shows the morphology before the salt spray test, and the right image shows the morphology after the salt spray test.
[0086] Check the rust condition of the coating surface according to the requirements of GB / T 1766-2008.
[0087] The evaluation criteria are as follows:
[0088] Ri0: 0% rust area, no rust.
[0089] Ri1: 0.05% rust area, very light rust.
[0090] Ri2: 0.5% rusted area, slightly rusted.
[0091] Ri3: 1% rusted area, obvious rust.
[0092] Ri4: 8% rust area, large rust.
[0093] Ri5: 40%-50% rusted area, severe rust.
[0094] Table 1:
[0095] Example Salt spray test (72 hours) Salt spray corrosion resistance rating Example 1 Yellow metal surface, no pitting, no rust Ri0 Example 2 Yellow metal surface, metal loss of gloss, a small amount of pitting Ri1 Example 3 Yellow metal surface, metal loss of gloss, a small amount of pitting Ri2 Example 4 Rough surface, metal loss of gloss, a small amount of pitting Ri2 Comparative Example 1 Rough surface with a lot of patina Ri5 Comparative Example 2 Rough surface with a lot of patina Ri5 Comparative Example 3 Rough surface with a small amount of patina Ri3 Comparative Example 4 Rough surface with a lot of patina Ri5 Comparative Example 5 Rough surface with a lot of patina Ri5 Comparative Example 6 Rough surface with a small amount of patina Ri3
[0096] The barrier properties of Example 1 and Comparative Example 1 were tested. The Example 1 and Comparative Example 1 were immersed in a 3.5% NaCl aqueous solution for 7 days, and then subjected to electrochemical impedance spectroscopy test. The test results are shown in the attached specification. Figure 11 、 12 , as shown in 13.
[0097] Figure 11 In the Nyquist diagram, the larger the radius of the capacitive reactance arc in the high frequency region, the better the barrier performance of the coating, which corresponds to better corrosion resistance. Figure 11 As shown, the order of the capacitive reactance arc radius in the high-frequency region is that Example 1 is greater than Comparative Example 1. It can be seen that the shielding performance of the coating obtained in Example 1 is better than that of Comparative Example 1.
[0098] In the Bode spectrum, the low-frequency impedance modulus (|Z|0.01Hz) in the electrochemical impedance test is a semi-quantitative indicator of the coating's ability to shield the penetration of corrosive media (water, oxygen, chloride ions, etc.). The larger the impedance modulus, the stronger the corresponding shielding performance against penetration of corrosive substances. Figure 12 、 13 As shown, the low-frequency impedance modulus of the coating obtained in Example 1 is obviously greater than that in Comparative Example 1, so its shielding effect against corrosive media is better.
[0099] These results demonstrate that the environmentally friendly, high-performance anti-corrosion coating for contact network copper components obtained by the present invention exhibits excellent corrosion resistance, is environmentally friendly and pollution-free, exhibits excellent durability, and exhibits excellent compatibility and adsorption with the substrate, effectively balancing other substrate properties. The preparation method disclosed herein is simple and effective, with broad applicability.
[0100] Obviously, the above embodiments are merely examples for illustrative purposes and are not intended to limit the implementation methods. Those skilled in the art will readily appreciate that other variations or modifications based on the above descriptions are possible. It is not necessary and impossible to enumerate all implementation methods here. However, any obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.
Claims
1. A method for preparing an environmentally friendly anti-corrosion coating for copper alloy contact network components, characterized in that: The specific process includes: 1) Use pre-corrosion treatment liquid to pre-corrode copper alloy contact network components; 2) a primary chromate passivation treatment; the copper alloy parts after the pre-corrosion treatment are passivated using a primary chromate passivation treatment solution, wherein the primary chromate passivation treatment solution comprises, by weight percentage, 10-20% arginine chromate, 0-1% sulfuric acid, 0-1% phosphoric acid, 0-10% polyethylene glycol, and the remainder water; 3) Secondary chromate passivation treatment: The copper alloy parts after the primary chromate passivation treatment are subjected to secondary chromate passivation treatment, wherein the secondary chromate passivation treatment solution comprises, by weight percentage, 1-5% chromic anhydride, 0-1% acetic acid, 1-5% copper sulfate, 1-5% sodium formate, and the remainder water; 4) Drying.
2. The method for preparing an environmentally friendly copper alloy catenary component anti-corrosion coating according to claim 1, characterized in that: The method comprises the following steps: preparing a pre-corrosion treatment liquid according to mass percentage, wherein the components thereof are: 0-5% glacial acetic acid, 0-5% concentrated hydrochloric acid, 0-5% sulfuric acid, and the remainder water; immersing the copper alloy parts in the pre-corrosion treatment liquid for 10-30 minutes, then rinsing the copper alloy parts with running water for 30-60 minutes, and repeating the above steps 1-5 times.
3. The method for preparing an environmentally friendly copper alloy catenary component anti-corrosion coating according to claim 1, characterized in that: After the pre-corrosion treatment, the copper alloy parts are immersed in a primary chromate passivation treatment solution or a secondary chromate passivation treatment solution for 10 to 30 minutes, and the copper alloy parts are rinsed with running water for 30 to 60 minutes. The above steps are repeated 1 to 5 times.
4. The method for preparing an environmentally friendly copper alloy catenary component anti-corrosion coating according to claim 1, characterized in that: The preparation method of arginine chromate comprises the following steps: adding arginine and sodium chromate to a mixed solvent of ethanol and water, stirring to obtain a mixed solution, then slowly dropwise adding 5 to 10% by weight of a 0.1 to 0.5 mol / L hydrochloric acid solution to the mixed solution, concentrating at 50 to 100 degrees Celsius, and then vacuum drying. The obtained product is washed with a mixed solution of ethyl acetate and petroleum ether in a mass ratio of 1:1 to 1:2, and then dried to obtain arginine chromate.
5. The method for preparing an environmentally friendly copper alloy catenary component anti-corrosion coating according to claim 1, characterized in that: The molecular weight of polyethylene glycol is 400-2000.
6. The method for preparing an environmentally friendly copper alloy catenary component anti-corrosion coating according to claim 1, characterized in that: The components of the pre-corrosion treatment solution, by weight percentage, are: 2% glacial acetic acid, 1% concentrated hydrochloric acid, 0.25% sulfuric acid, and the balance is water; and / or, the components of the primary chromate passivation treatment solution, by weight percentage, are: 30% arginine chromate, 1% sulfuric acid, 1% phosphoric acid, 5% polyethylene glycol, and the balance is water; The components of the secondary chromate passivation treatment solution are as follows by mass: 3% chromic anhydride, 1% acetic acid, 2% copper sulfate, 1% sodium formate, and the remainder water.